#### Answer

-6

#### Work Step by Step

We are given that $f(x)=-2x^{2}+3x-6$. In order to evaluate at $f(0)$, we can plug 0 into the function and evaluate.
$f(0)=-2(0)^{2}+3(0)-6=-2(0)+0-6=0+0-6=-6$

Published by
Pearson

ISBN 10:
0321969359

ISBN 13:
978-0-32196-935-4

-6

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.